Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.7314/apjcp.2013.14.6.3855
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Efficacy of Curcumin in Liver Cancer

Abstract: Purpose: Liver cancer, one of the most common cancers in China, is reported to feature relatively high morbidity and mortality. Curcumin (Cum) is considered as a drug possessing anti-angiogenic, anti-inflammation and anti-oxidation effect. Previous research has demonstrated antitumor effects in a series of cancers. Materials and Methods: In this study the in vitro cytotoxicity of Cum was measured by MTT assay and pro-apoptotic effects were assessed by DAPI staining and measurement of caspase-3 activity. In viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Data are presented as means ± standard deviation (SD). We have enough experience in conducting medical researches, and have published some results elsewhere Dai et al, 2013;Deng et al, 2013;Gu et al, 2013;Fei et al, 2013;Shen et al, 2013;Sun et al, 2013;Wei et al, 2013;Yan et al, 2013;Gong et al, 2014;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Data are presented as means ± standard deviation (SD). We have enough experience in conducting medical researches, and have published some results elsewhere Dai et al, 2013;Deng et al, 2013;Gu et al, 2013;Fei et al, 2013;Shen et al, 2013;Sun et al, 2013;Wei et al, 2013;Yan et al, 2013;Gong et al, 2014;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The above hypothesis test was a two-sided test; P<0.05 was considered as statistically significant. We have enough experience in conducting medical researches, and have published some results elsewhere Yan et al, 2011;Zhang et al, 2011;Gong et al, 2012;Liu et al, 2012;Gu et al, 2013;Shu et al, 2012;Xu et al, 2012;Xu et al, 2012;Yu et al, 2012;Zhang et al, 2012;Chen et al, 2013;Dai et al, 2013;Deng et al, 2013;Huang et al, 2013;Lu et al, 2013;Sun et al, 2013;Wei et al, 2013;Wu et al, 2013;Yang et al, 2013;.…”
Section: Statistical Methods and Research Experiencementioning
confidence: 99%
“…Curcumin (CUR), the active component of turmeric has potent anti-tumor effects to hepatocarcinoma in clinical trials (Dai et al, 2013) and several other cancers, such as colon cancer (Lee et al, 2009) and breast cancer (Mehta et al, 1997). Although CUR is remarkably non-toxic and has promising anti-cancer activities, preclinical and clinical studies indicated that its poor bioavailability and pharmacokinetic profiles due to its instability under physiological conditions had limited its application in anti-cancer therapies (Anand et al, 2007;Appiah-Opong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%